Surface chemistry of La0.6Sr0.4CoO3−δ thin films and its impact on the oxygen surface exchange resistance. Issue 45 (14th October 2015) - Rupp, Ghislain M.; Téllez, Helena; Druce, John; Limbeck, Andreas; Ishihara, Tatsumi; Kilner, John; Fleig, Jürgen
Abstract : Correlation between the surface chemistry of LSC thin films analyzed by LEIS and ICP-MS and the oxygen exchange kinetics. Abstract : The surface composition of dense La0.6 Sr0.4 CoO3− δ (LSC) thin film model electrodes, deposited by pulsed laser deposition at 600 °C on yttria-stabilized zirconia (100) electrolytes, was investigated by low-energy ion scattering (LEIS) and time resolved inductively coupled plasma mass spectrometry (ICP-MS). Results obtained by both methods agree qualitatively and quantitatively and provide a comprehensive picture of the surface composition and cation diffusion kinetics of LSC. The measurements revealed that freshly prepared LSC thin films already show a Sr-rich and Co-poor termination layer (80% Sr surface coverage). This Sr-rich surface layer was proven to be an equilibrium property of LSC as it forms again at elevated temperatures after removal. The kinetics of this surface reconstruction is surprisingly fast (<1 h at 550 °C) and indicates high Sr mobility in LSC. Electrochemical Impedance Spectroscopy (EIS) measurements at 400 °C revealed the detrimental effect of this surface layer on the oxygen surface exchange and suggest that higher Co concentrations in the termination layer facilitate the oxygen exchange reaction.